Web-Based Solution for Mapping Application using Open-Source Software Server - Jyoti Sarup; Vimal Shukla (International Journal of Informatics and Communication Technology (IJ-ICT), 2012)
Web GIS is an advance technology to manage and display all geographical locations on the earth surface. This paper deals with road analysis, to find the shortest path of route etc. so that these types of information can be displayed using Geographical Information System (GIS) technique. The approach combines both spatial and non-spatial data. This paper highlight, the suitability to handle spatial and non-spatial attributes of road features and to display and publish in web based GIS platform. This also commences the suitable software server. This paper deals with Web mapping application using different free tools and Open Source Software server (FOSS) and provides the free server solutions. Open-source software has the advantages of low cost, high stability and security, so it is preferred by the small and medium-sized Web GIS project. In this paper Web based Web-GIS architecture is described and implemented using open source Web-GIS tools like GeoServer, PostGIS and OpenLayers. An area of Bhopal City, M.P. Nagar has been chosen and road network was created in Q-GIS and published in WebGIS Server solutions. This has been used for centralized visualization of geospatial data present in various spatial databases located in different locations. This may have help to developing countries which cannot afford to use such solution. Hence there was a necessity of an open source Web-GIS application that should be both powerful for visualizing and cost effective.DOI: http://dx.doi.org/10.11591/ij-ict.v1i2.1490